2021
DOI: 10.1002/pssr.202100085
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Powered Ultraviolet Photodetector with Ultrahigh Photoresponsivity (208 mA W−1) based on SnO2 Nanostructures/Si Heterojunctions

Abstract: The development of high‐performance, self‐powered ultraviolet (UV) photodetectors (PDs) is of utmost interest for military and industrial applications. Herein, a novel design scheme for enhancing the performance of self‐powered PDs based on the p–n heterojunction is proposed. The device architecture is engineered by integrating a nanostructured SnO2 layer into the n‐SnO2/p‐Si heterojunction. The resulting device yields an impressively high photoresponsivity of 22.73 A W−1, a large external quantum efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is worth mentioning that, Ma et al reported a broadband photodetector and shown enhanced UV photodetection performance based on a Ga 2 O 3 /BFO heterojunction [19]. Thereinto, the heterojunction photodetectors are extensively studied for achieving selfpowered operation mode due to the formation of built-in electrical field at the heterointerface [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that, Ma et al reported a broadband photodetector and shown enhanced UV photodetection performance based on a Ga 2 O 3 /BFO heterojunction [19]. Thereinto, the heterojunction photodetectors are extensively studied for achieving selfpowered operation mode due to the formation of built-in electrical field at the heterointerface [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to conventional heterojunction theory [53,54], the expression for depletion layer capacitance is given by, e e e e = + -…”
Section: Resultsmentioning
confidence: 99%
“…Here, the values of N c and N v are 3.716 × 10 18 and 1.04 × 10 19 cm −3 , respectively [42,46]. In addition, the values of the built-in potentials on the n-side (V dn ) and p-side (V dp ) components can be calculated by formulas (10) and (11), respectively [42] V…”
Section: Resultsmentioning
confidence: 99%
“…In a simple way, a p-n heterojunction can be formed by depositing MO x on a semiconductor substrate, which provides a promising structure for photodiodes, solar cells, photodetectors, and sensors [4][5][6][7][8][9][10]. In particular, MO x semiconductors can be employed as an n-type emitter layer for developing the UV p-n heterojunction photodetectors (HPDs) owing to their advantages, including intrinsic visible-blind property, high radiation resistance, and excellent transparency in visible region [11][12][13].…”
Section: Introductionmentioning
confidence: 99%